Management of Local Broadcast Production and Enforcement of P3SPS by Indosiar Ambon TV - Sopacua, Yustina; Alfredo, Ronald; Tahalele, Olivia (MultiTech Publisher, 2023)
The research investigates management of local broadcast production and P3SPS (Broadcasting Code of Conduct and Broadcast Program Standards) enforcement by Indosiar TV. Four stakeholders were interviewed: Indosiar TV Ambon representatives, KPID [Regional Indonesian Broadcasting Commission] Maluku Chairperson, P3SPS Department, and community members. Primary data collected through interviews and documentation; secondary sources included web, social media, books, and journals. Research process involved pre-research media observation, field research, data categorization, and objective conclusions. Aimed at benefiting the community by preventing policy duplication and aiding grassroots execution in broadcasting.